Klotho Inhibits Unilateral Ureteral Obstruction-Induced Endothelial-to-Mesenchymal Transition via TGF-β1/Smad2/Snail1 Signaling in Mice - Li, Shasha; Yu, Lixia; He, Aolin; Liu, Qifeng (Frontiers in Pharmacology, 2019)
This study aimed to evaluate repression of Klotho on unilateral ureteral obstruction (UUO)-induced renal fibrosis and endothelial-to-mesenchymal transition (EndoMT) in mice. Renal fibrosis model was established by UUO in C57BL/6 male mice. Recombinant Klotho protein was administered to UUO mice as treatment group, and the mice in sham and UUO group were administered with an equal volume of vehicle. EndoMT biomarkers and TGF-β1/Smad2/Snail1 signaling were examined by immunofluorescence, immunohistochemistry, and western blotting assays. UUO deteriorated kidney function and resulted in increased expression of the mesenchymal marker α-smooth muscle actin and decreased expression of vascular endothelial cadherin, an endothelial marker. Moreover, UUO enhanced TGF-β1, phosphorylated Smad2 (p-Smad2), and Snail1 expression. Interestingly, Klotho treatment suppressed UUO-induced TGF-β1, p-Smad3, and Snail1 expression, which was accompanied by alleviation of the EndoMT process. Our findings demonstrated that Klotho significantly ameliorated EndoMT progression by targeting TGF-β1/Smad/Snail1 signaling in UUO mice, which provides the possibility for Klotho-based therapeutic protection against renal fibrosis.